Evidence That the Talk Test Can Be Used to Regulate Exercise Intensity. Issue 5 (May 2015) - Woltmann, Michaela L.; Foster, Carl; Porcari, John P.; Camic, Clayton L.; Dodge, Christopher; Haible, Stephanie; Mikat, Richard P.
Abstract : Abstract: Woltmann, ML, Foster, C, Porcari, JP, Camic, CL, Dodge, C, Haible, S, and Mikat, RP. Evidence that the talk test can be used to regulate exercise intensity. J Strength Cond Res 29(5): 1248–1254, 2015—The Talk Test (TT) has been shown to be a surrogate of the ventilatory threshold and to be a viable alternative to standard methods of prescribing exercise training intensity. The TT has also been shown to be responsive to manipulations known to change physiologic function including blood donation and training. Whether the TT can be used independently to regulated training intensity is not known. Physically active volunteers ( N = 16) performed an incremental exercise test to identify stages of the TT (Last Positive [LP], Equivocal [EQ], and Negative [NEG]). In subsequent, randomly ordered, 30-minute steady-state runs, the running velocity was regulated solely by "clamping" the TT response desired and then monitoring the response of conventional markers of exercise intensity (heart rate, blood lactate, rating of perceived exertion). All subjects were able to complete the LP stage, but only 13 of 16 and 2 of 16 subjects were able to complete the EQ and NEG stages, respectively. Physiologic responses were broadly within those predicted from the incremental exercise test and within the appropriate range of physiologic responses for exercise training. Thus, in addition to correlating with convenient physiological markers, the TT can be used proactively to guide exercise training intensity. The LP stage produced training intensities compatible with appropriate training intensity in healthy adults and with recovery sessions or long duration training sessions in athletes. The EQ and NEG stages produced intensities compatible with higher intensity training in athletes. The results demonstrate that the TT can be used as a primary method to control exercise training intensity.